2017
DOI: 10.2174/1570162x15666170320112247
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Functional Assays as Measures of Fc Receptor-Mediated Immunity to HIV - New Technologies and their Impact on the HIV Vaccine Field

Abstract: Background:There is now intense interest in the role of HIV-specific antibodies and the engagement of FcγR functions in the control and prevention of HIV infection. The analyses of the RV144 vaccine trial, natural progression cohorts, and macaque models all point to a role for Fc-dependent effector functions, such as cytotoxicity (ADCC) or phagocytosis (ADCP), in the control of HIV. However, reliable assays that can be reproducibly used across different laboratories to measure Fc-dependent functions, such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 163 publications
0
26
0
Order By: Relevance
“…Here we provide evidence that anti-cluster A and anti-CoRBS Abs collaborate in engaging the dimeric form of the Fc␥RIIIa receptor when bound to the cognate epitopes within the same monomeric gp120. We utilized a novel probe, a covalent Fc␥RIIIa dimer, as a surrogate of Fc␥RIIIa present on effector cells (11,37,39,40,61) and showed that sequential binding of antibodies specific for these two CD4i epitope targets is required for effective receptor engagement and potent ADCC. Recent structural studies defined the Env epitopes recognized by anticluster A and anti-CoRBS Abs at the atomic level and mapped the cluster A epitope region to the C1-C2 regions of the gp120 inner domain in its CD4-bound conformation (12,32,33,62) and CoRBS to the bridging sheet and the base of the V3 loop of the CD4-triggered gp120 (63-65).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we provide evidence that anti-cluster A and anti-CoRBS Abs collaborate in engaging the dimeric form of the Fc␥RIIIa receptor when bound to the cognate epitopes within the same monomeric gp120. We utilized a novel probe, a covalent Fc␥RIIIa dimer, as a surrogate of Fc␥RIIIa present on effector cells (11,37,39,40,61) and showed that sequential binding of antibodies specific for these two CD4i epitope targets is required for effective receptor engagement and potent ADCC. Recent structural studies defined the Env epitopes recognized by anticluster A and anti-CoRBS Abs at the atomic level and mapped the cluster A epitope region to the C1-C2 regions of the gp120 inner domain in its CD4-bound conformation (12,32,33,62) and CoRBS to the bridging sheet and the base of the V3 loop of the CD4-triggered gp120 (63-65).…”
Section: Discussionmentioning
confidence: 99%
“…cells to clear infected cells, such as (i) the strength of IgG interactions with Fc␥Rs; (ii) the density of IgG opsonization; and (iii) the orientation of the Fc portion (11,12). Additionally, the interaction of Fc␥Rs with Abs bound to distinct epitopes may have additive or synergistic effects on host immune responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, these techniques also present limitations, owing to the long execution, complexity and difficulty of reproduction and standardization across laboratories; in addition, the results of the assays may be biased by the possible presence of polymorphisms in the Fc-receptor of effector cells collected from human donors. 118 This review focuses on the main aspects of T-and B-cell responses following influenza vaccination, as evaluated by means of flow cytometry. Hence, efforts should be made to identify other immunological parameters, such as Tcellmediated immune response, as correlates of protection, especially in view of the fact that the scenario of influenza vaccine is evolving rapidly and novel influenza vaccines will probably be developed in the foreseeable future.…”
Section: Resultsmentioning
confidence: 99%
“… 21 Stephen Kent (University of Melbourne) developed a novel Fc-receptor dimer assay for measuring Fc mediated effector functions of anti-HIV antibodies derived from natural infection or elicited by vaccination. 22 The Fc-receptor dimer assay could be conducted in a robust and reproducible manner with results that were highly correlated with results from several different assay types that measured antibody-dependent cell-mediated cytotoxicity (ADCC). 22 The Global HIV Vaccine Enterprise held a workshop during the symposia entitled, “Knowns and Unknowns of Assaying ADCC against HIV” that discussed the various ADCC assays used to assess immune responses induced by HIV vaccine candidates in clinical and pre-clinical trials.…”
Section: Introductionmentioning
confidence: 98%